Teori Konstruktivisme - Teguh Handoyo; Ani Ani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Constructivism learning theory places learners as active subjects in constructing knowledge through learning experiences, social interactions, and reflection on their surroundings. This approach views learning not as a passive process of receiving information, but as an active process of constructing meaning based on the prior knowledge possessed by learners. This paper aims to comprehensively examine the development and definition of constructivist learning theory, its main principles and characteristics, and its implications in the learning process, particularly in the context of primary education. The writing method used is a literature study by analyzing various literature sources in the form of textbooks, scientific journal articles, and other relevant references related to constructivism theory. The results of the study show that constructivist learning emphasizes learner-centered learning, where knowledge is not transferred directly by the teacher but is constructed through a process of assimilation and accommodation. In this approach, teachers act as facilitators who design a conducive learning environment so that students are able to build understanding independently and through social interaction. The application of constructivist learning has been proven to encourage the development of critical thinking, problem solving, cooperation, and meaningful learning. Therefore, constructivist learning theory is relevant to be applied in modern learning as an effort to improve the quality of the learning process and outcomes of students.